Edukasi DAGUSIBU untuk Meningkatkan Literasi Pengelolaan Obat pada Siswa SMP Negeri 20 Kendari Melalui Gerakan Sadar Pengelolaan Obat Mandi (GESPO-MANDIRI) - A Sida, Nurramadhani; Hasnawati; Henny Kasmawati; Sabarudin; Nita Trinovitasari; Rifa'atul Mahmudah; Aswani (Jurnal Transformasi Digital Masyarakat (DIGIMAS), 2026)
Rational drug use is an important component in improving public health. However, literacy related to medicine management remains low, particularly among school-aged adolescents who are beginning to develop independence in maintaining their health. Limited understanding of how to obtain, use, store, and dispose of medicines may increase the risk of inappropriate medicine use. Therefore, DAGUSIBU education needs to be introduced early as a promotive and preventive effort. This community service activity aimed to improve the knowledge and understanding of students at SMP Negeri 20 Kendari regarding proper, safe, wise, and rational medicine management in daily life. The activity was conducted as DAGUSIBU education on April 30, 2026, at SMPN 20 Kendari for two hours, involving 25 eighth-grade students. The activity included a pretest, material delivery through a lecture supported by PowerPoint and leaflets, discussion, question-and-answer sessions, and a posttest using a modified instrument. The results showed an increase in students’ knowledge after DAGUSIBU education. The average correct answers increased from 11.5 or 46% in the pretest to 24.6 or 98.4% in the posttest. Improvements occurred in all indicators, particularly in understanding the term DAGUSIBU, official sources for obtaining medicines, storage, dosage, directions for use, and disposal of expired medicines. In conclusion, DAGUSIBU education can improve students’ understanding of proper medicine management.